Penerapan Pendidikan Berbasis Masyarakat di Rumah Tahfiz al-Syamsiyah Sukoharjo Tahun 2016 - Arif, Mohamad Slamet, Dr. Ari Anshori, M.Ag (2017)
The education policy in Indonesia in 1990 had centralistic characteristic. Such policy made the education not having inclusive response power to societies' needs the problems they are faced so that the implication policy created the varieties of education model such as Community-Based ducation (CBE). One of education models based on societies being succes or ful in play its role as society study centre is a religious model. The religious model has function as a religious education, social, or potential a development agency of community potential. al-Syamsiyah Taḥfīẓ House at Gobayon Sukoharjo is one of religious agencies based on societies because its purpose is as the answer to societies' needs is scarcity of religious institutions which have a concern on Taḥfīẓ Qur'ān especially that for students in Surakarta.The problem which identifies this research is how to apply Community-Based Education in al-Syamsiyah Taḥfīẓ House with the any obstacle which is faced in organizing process. The purpose of research is to elaborate how is the application of Community-Based Education in al-Syamsiyah Taḥfīẓ House constraints are faced during the implementation process of education. The research has used a qualitative method and the data collection used interview, observation, and documentation. Methods to analyze data has been used the qualitative descriptive technique.Based on the research result, writer finds the community-based education in al-Syamsiyah Taḥfīẓ House is aplied through four pplications in the fields of curriculum, daily activities, community empowerment, and societies participation role in organizing process. This application has the purpose to develop the students more competent and more skilled to meet societies' needs. The problems in organizing process in Taḥfīẓ al-Syamsiyah House is the lack of community care and the students need motivation to be more active in memorizing al-Qur'ān.Keywords: Community-Based Education, al-Syamsiyah Taḥfīẓ House at Gobayon Sukoharjo, Religious Model.